2018
DOI: 10.1172/jci.insight.120360
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific MHC-II expression drives a unique pattern of resistance to immunotherapy via LAG-3/FCRL6 engagement

Abstract: Bristol-Myers Squibb, and Genentech. JAS is a compensated member of the advisory boards of Bristol-Myers Squibb, Pfizer, Array, Genentech, Incyte, and Curis and has received research support from Pfizer, Bristol-Myers Squibb, and Curis. PBF receives research funding from Incyte. JMB, MES, MVE, VS, and DBJ are coauthors on a patent pending for use of MHC-II to predict responses from immunotherapy (15/376,276). RSD, DMS, DBJ, and JMB are coauthors on a patent pending for use of FCRL6 antibodies for cancer therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 58 publications
3
115
0
1
Order By: Relevance
“…An increasing number of studies are linking PD‐1/LAG‐3 co‐expression in T cells to resistance to anti‐PD‐L1/PD‐1 therapies (Mishra et al , ; Huang et al , ; Williams et al , ; Johnson et al , ). Our study prompts the clinical evaluation of patients with systemic CD4 T‐cell dysfunctionality by PD‐1/LAG‐3 dual‐blockade strategies.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies are linking PD‐1/LAG‐3 co‐expression in T cells to resistance to anti‐PD‐L1/PD‐1 therapies (Mishra et al , ; Huang et al , ; Williams et al , ; Johnson et al , ). Our study prompts the clinical evaluation of patients with systemic CD4 T‐cell dysfunctionality by PD‐1/LAG‐3 dual‐blockade strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Both CD4 and CD8 dysfunctionality in G2 patients could be reverted ex vivo by PD-1/LAG-3 coblockade. An increasing number of studies are linking PD-1/LAG-3 co-expression in T cells to resistance to anti-PD-L1/PD-1 therapies (26)(27)(28)(29). Our study suggests that patients with dysfunctional CD4 immunity should undergo alternative treatments to recover CD4 immunity and enhance CD8 T cell functionality.…”
Section: Discussionmentioning
confidence: 78%
“…FCRL6 possess an intracellular immunoreceptor tyrosinebased inhibition motif (ITIM), implying that FCRL6 transmits inhibitory signaling cascades. A recent study identified high levels of FCRL6 on NK cells in HLA-II + solid tumor environment, and expression of HLA-DR molecules on the surface of K562 cells inhibited the cytotoxic function of FCRL6 + NK-92 cells (Johnson et al, 2018). Interestingly, FCRL6 is down-modulated on the surface of NK cells upon exposure to IL-2 and IL-15 (Wilson et al, 2007), in contrast to NKp44, which expression is induced after stimulation with these cytokines.…”
Section: Hla Class II Molecules Can Serve As Ligands For Nk Cell Recementioning
confidence: 97%
“…The level of HLA-II expression within the tumor environment can predict patient responses toward anti-PD-1 immunotherapy (Johnson et al, 2016). Interestingly, high FCRL6 expression has been detected on NK cells within HLA-II + solid tumors, and blocking of FCRL6 increased the functional response of NK cells as well as T cells toward HLA-DR + tumor cells (Johnson et al, 2018). In addition, FCRL6 levels were elevated at relapse within patients that progressed under anti-PD-1therapy (Johnson et al, 2018).…”
Section: Hla-ii Molecules In Malignancies and Auto-inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation